Towards a comparative institutionalism forms, dynamics and logics across the organizational fields of health care and higher education - Pinheiro, Rómulo (Research in the sociology of organizations ;, 2016)
The book examines ongoing dynamics within the organizational fields of health and higher education, with a focus on collective (public universities and hospitals) and individual (professionals) actors, structures, processes and institutional logics. The fact that universities and hospitals share a number of important characteristics, both being hybrid organizations, professional bureaucracies, and operating within highly institutionalised environments, they are also characterised by their distinctive features such as the importance attributed to scientific autonomy and prestige (universities) and the needs and expectations of users and funders (hospitals). The volume brings together two relatively distinct scholarly traditions within the social sciences, namely, scholars - sociologists, educationalists, economists, political scientists and public administration researchers, etc. - involved with the study of change dynamics within the fields of health care and higher education in Europe and beyond. The authors resort to a variety of theoretical and conceptual perspectives emanating from the studies of organizational fields more generally and neo-institutionalism in particular.